(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Strong, extensive, and active bond markets are required to sustain credit requirements, improve a country's financial system stability, and decrease corporate sector financial crises—all of which are critical for the growth of the economy. Since this benefits investors, corporations, and governments, the current study concentrates on the expansion of the Indian bond market and its effects on specific monetary, fiscal, and economic variables from January 1, 2012, to March 31, 2024. With yield rate acting as the dependent variable and monetary, fiscal, and economic variables acting as independent variables, the study makes use of secondary data. The analysis finds a strong positive and negative relationship between a well-developed bond market and several fiscal, monetary, and economic variables. The results indicate that, out of all the parameters chosen, the reverse repo rate (RRR), repo rate (RR), interest rate (IR), wholesale price index (WPI), and consumer price index (CPI) have the biggest effects on yield rates in India. According to the analysis, these factors have complicated causal connections and feedback loops that can have a direct or indirect impact on yield rates when they change.